A nitrogen-doped carbon-coated amorphous silicon monoxide / carbon nanofiber composite negative electrode material and a preparation method thereof
Patent Information
- Application Number
- CN202611224595.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-20
AI Technical Summary
尽管这些方法在一定程度上延缓了SiOx颗粒粉化脱离电极、克服了材料本征电导率低等问题,但是,其要应用到高性能的锂离子电池负极材料领域,以下根本缺陷仍然无法克服:①上述碳材料仅是环绕在SiOx颗粒周围,其对SiOx颗粒的直接束缚力有限,无法有效限制粉化后颗粒的脱落,仍会导致活性物质利用率降低及容量较快衰减;②材料与SiOx颗粒接触面积小且牢固性差,加剧了电极界面的电化学极化,增大了体系的欧姆内阻,降低了复合材料在大电流充放电下维持高可逆比容量与倍率响应的能力;③普通碳材料和电解液间的浸润性较差,导致界面电荷转移阻抗升高,锂离子吸附与嵌储活性位点减少,赝电容容量降低等一系列问题;④电极仍需采用额外的集流体,降低了全电池的质量能量密度
①无定形氧化亚硅颗粒在三维纳米纤维网络内部的均匀分散与牢固限域,有效阻止了硅基颗粒在充放电过程中的团聚与粉化破裂,同时PANI在SiOx表面的包覆层不仅进一步阻止了SiOx的流失,同时还提高了和SiOx的接触面积,降低了接触电阻,提高了电极的导电性和倍率性能;②内部的纳米纤维骨架与外层原位生长的聚苯胺衍生碳层相互贯通,构建了双重导电网络,大大降低了材料的电荷转移阻抗,提高了倍率性能和电子传递效率;③三维纳米纤维网络内部富含的微观柔性间隙,为氧化亚硅剧烈的体积变化提供了充足的弹性缓冲空间,确保了电极在长期循环中的结构完整性;④该复合材料呈现三维互通的自支撑结构,可直接作为无集流体、无粘结剂、无导电剂的自支撑极片使用,有效减少了电极中非活性物质的质量占比,使得全电池的整体质量能量密度得到提升;⑤氮掺杂的存在带来丰富的缺陷活性位点,可显著提高碳壳层与电解液之间的浸润性,从而加速锂离子的扩散动力学;⑥无定形SiOx相比于结晶纯硅更低的体积膨胀率和更好的各向同性膨胀性质与外部双重碳结构的限域缓冲效应相协同,进一步保障了电极的稳定性。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical energy storage materials technology, and specifically relates to a nitrogen-doped carbon-coated amorphous silicon suboxide / carbon nanofiber composite anode material and its preparation method. Background Technology
[0002] Driven by global energy shortages and the "dual-carbon" policy, the market demand for efficient and clean energy storage equipment is growing rapidly. Lithium-ion batteries, with their comprehensive performance advantages such as high energy density, no memory decay, and environmental friendliness, have become the most mature commercially available energy storage device with the widest range of applications. Among various battery anode materials, the theoretical specific capacity of commercially available traditional graphite anodes is only 372 mAh / g, and their electrochemical performance is approaching its theoretical upper limit, making it difficult to meet the needs of large-scale production of next-generation high-energy-density power batteries. Compared to graphite, silicon anode materials have a theoretical specific capacity as high as 3580 mAh / g in room-temperature electrochemical systems, exhibiting a significant advantage in lithium storage capacity. However, due to the extremely drastic volume expansion (300%–400%) during charging and discharging, severe particle pulverization, conductive network peeling and breakage, and repeated rupture and reconstruction of the solid electrolyte interphase (SEI) film occur, leading to a precipitous drop in capacity. To overcome this intrinsic defect of pure silicon, silicon suboxide (SiO2) is used. x As a compromise, silicon suboxide (SiO2) has received widespread attention from researchers. x During the initial lithium insertion process, inactive Li₂O and lithium silicate can be generated in situ, which can alleviate stress to some extent and exhibit better cycle stability than pure silicon, thus attracting widespread attention from researchers. However, micron-sized amorphous silicon suboxide still undergoes a volume expansion of approximately 160% to 200% during charge and discharge, making it prone to pulverization, breakage, and detachment from the electrode structure, leading to reduced utilization of active materials and rapid capacity decay. Furthermore, the extremely low intrinsic conductivity of amorphous silicon suboxide further limits its application in high-performance energy storage batteries.
[0003] To improve the electrochemical performance of silicon suboxide materials, it is common practice to combine silicon suboxide with materials such as graphene, carbon nanotubes, and carbon nanofibers. Although these methods delay the degradation of SiO₂ to some extent... x While the pulverization and detachment of the particles from the electrode overcomes problems such as low intrinsic conductivity, the following fundamental defects remain unresolved for its application in high-performance lithium-ion battery anode materials: ① The aforementioned carbon materials merely surround SiO2. x Around the particles, it affects SiO x The direct binding force of the particles is limited and cannot effectively prevent the detachment of particles after pulverization, which will still lead to a decrease in the utilization rate of active materials and a rapid capacity decay; ② Material and SiO xThe small contact area and poor adhesion of the particles exacerbate the electrochemical polarization at the electrode interface, increase the ohmic resistance of the system, and reduce the ability of the composite material to maintain high reversible specific capacity and rate response under high current charge and discharge. ③ Poor wettability between ordinary carbon materials and the electrolyte leads to increased interfacial charge transfer impedance, reduced lithium-ion adsorption and intercalation sites, and decreased pseudocapacitance, among other problems. ④ An additional current collector is still required for the electrode, reducing the overall energy density of the battery. These problems ultimately prevent a fundamental solution to the limitations of composite anode materials in terms of electron transport capability, unsatisfactory charge-discharge cycle life, and low energy density under high-rate charge and discharge. Therefore, the development of a stable coating material for SiO2 is crucial. x Improving the conductivity, reducing interfacial impedance, enhancing wettability with electrolyte, eliminating the need for external binders and conductive agents, and requiring no additional current collectors are critical technical challenges that urgently need to be addressed in this field. Summary of the Invention
[0004] To address the above problems, this invention provides a nitrogen-doped carbon-coated amorphous silicon suboxide / carbon nanofiber composite anode material and its preparation method, solving the following problems: ①SiO x The particles are uniformly dispersed and effectively bound within the three-dimensional network inside the NCNF, effectively suppressing the drastic volume expansion, pulverization, and detachment from the conductive network during charging and discharging. Secondly, the flexible internal NCNF framework and the nitrogen-doped carbon layer (NC) derived from the thermal decomposition of polyaniline (PANI) after in-situ polymerization are interconnected, constructing a dual continuous conductive network from the inside out. This significantly reduces the electrochemical polarization of the material and improves its overall electronic conductivity and rate performance. Thirdly, the NCNF framework and the external NC form an interfacial synergistic mechanism. During lithium insertion / extraction, the dense outer carbon shell provides local physical confinement, directly coating the pulverized SiO₂. x The particles isolate the electrolyte to maintain the stability of the SEI film, while the flexible pores of NCNF act as stress absorption cells to dissipate the deformation stress conducted by the carbon shell, successfully solving the problem of SiO₂ after pulverization. x The shedding of particles ensures the structural integrity of the self-supporting electrode during long-term electrochemical cycling; ④ The polyacrylonitrile (PAN) and nitrogen-doped carbon derived from the outer PANI layer generate abundant defect active sites, which improves the interfacial wettability between the composite electrode material and the electrolyte, increases the active sites for lithium ion adsorption and intercalation, improves the pseudocapacitance of the material, and accelerates the diffusion kinetics of lithium ions; ⑤ The composite material presents an interwoven network fiber structure, which can be directly used as a self-supporting electrode without current collectors, binders, or conductive agents, which is beneficial to improving the mass energy density of the full battery.
[0005] A nitrogen-doped carbon-coated amorphous silicon suboxide / carbon nanofiber composite anode material, wherein the composite anode material exhibits a three-dimensional network fiber structure, with NCNF formed by carbonization of PAN fibers as the internal conductive framework, and amorphous SiO2. x The particles are uniformly dispersed within the fiber network structure, including NCNF and SiO. x The outer surface of the particles is coated with a nitrogen-doped carbon layer (NC) derived from the in-situ polymerization of polyaniline (PANI) followed by high-temperature carbonization and decomposition.
[0006] The amorphous silica particles have a particle size between 0.05 and 10 μm.
[0007] The diameter of the internal nitrogen-doped carbon nanofiber framework is 100-600 nm.
[0008] The thickness of the nitrogen-doped carbon layer covering the outer surface is 5-50 nm.
[0009] The composite negative electrode material contains 50-70 wt% amorphous silicon suboxide particles.
[0010] The carbon content in the composite anode material is 30-50 wt%.
[0011] A method for preparing a nitrogen-doped carbon-coated amorphous silicon suboxide / carbon nanofiber composite anode material, the specific preparation process of which is as follows: 1) SiO x Preparation of PAN composite fibers: Weigh 0.2-1 g of amorphous silica particles and place them in 5-10 mL of DMF. Disperse ultrasonically for 1-2 h. Add 0.5-2.0 g of PAN and dissolve it in the dispersion. Disperse ultrasonically at room temperature and stir magnetically for 10-20 h to obtain a uniformly mixed spinning solution. Transfer the spinning solution to a syringe and perform electrospinning at a high voltage of 10-25 kV, a feed rate of 0.5-2.0 mL / h, and a receiving distance of 10-25 cm. After drying, obtain SiO₂. x / PAN composite fiber; 2) SiO x Preparation of PAN@PANI composite fibers: Measure 3-8 mL of aniline monomer and 0.5-2 mL of concentrated hydrochloric acid and add them to 100-200 mL of deionized water. Stir magnetically to mix evenly and form a monomer solution. Add the SiO2 prepared and cut in step ①... xThe PAN fiber membrane was completely immersed in the monomer solution and allowed to stand at room temperature for 1-5 hours to achieve adsorption stability. Then, an oxidant solution was slowly added dropwise to the reaction system. This oxidant solution was prepared by dissolving 3-8 g of ferric chloride in 30-80 mL of deionized water containing 1-3 mL of concentrated hydrochloric acid. The polymerization reaction was carried out at room temperature for 6-12 hours. After the reaction, the product was washed and dried to obtain SiO₂. x / PAN@PANI composite fiber; 3) Multi-stage pre-oxidation stabilization treatment: The dried SiO2 from step 2) is then subjected to a multi-stage pre-oxidation stabilization treatment. x The PAN@PANI composite fiber membrane was placed in a muffle furnace and subjected to multi-stage pre-oxidation treatment in an air atmosphere. The temperature was increased to 80-110 ℃ at a heating rate of 1-5 ℃ / min and held for 0.5-2 h. Then, the temperature was increased to 150-200 ℃ at a heating rate of 1-5 ℃ / min and held for 0.5-2 h. Finally, the temperature was increased to 250-300 ℃ at a heating rate of 1-5 ℃ / min and held for 1-4 h. After the treatment, the membrane was cooled with the furnace to obtain the stabilized pre-oxidized product. 4) SiO x Preparation of / NCNF@NC composite anode material: The pre-oxidized product prepared in step 3) is heated to 700-1000 ℃ under an inert gas protective atmosphere at a heating rate of 1-5 ℃ / min and heat-treated for 2-6 h. After cooling with the furnace, nitrogen-doped carbon-coated amorphous silicon suboxide / carbon nanofiber composite anode material can be obtained.
[0012] The present invention has the following beneficial technical effects: ① The uniform dispersion and firm confinement of amorphous silica suboxide particles within the three-dimensional nanofiber network effectively prevents the aggregation and pulverization of silicon-based particles during charging and discharging. Simultaneously, PANI in SiO x The surface coating not only further prevents SiO x The loss of SiO2 also increased the yield of SiO2. x① The increased contact area reduces contact resistance and improves electrode conductivity and rate performance; ② The internal nanofiber skeleton and the outer in-situ grown polyaniline-derived carbon layer are interconnected, constructing a dual conductive network, which greatly reduces the charge transfer impedance of the material and improves rate performance and electron transfer efficiency; ③ The abundant microscopic flexible gaps within the three-dimensional nanofiber network provide sufficient elastic buffer space for the drastic volume changes of silicon suboxide, ensuring the structural integrity of the electrode during long-term cycling; ④ The composite material exhibits a three-dimensional interconnected self-supporting structure, which can be directly used as a self-supporting electrode without current collectors, binders, or conductive agents, effectively reducing the mass proportion of inactive materials in the electrode and improving the overall mass energy density of the full battery; ⑤ The presence of nitrogen doping brings abundant defect active sites, which can significantly improve the wettability between the carbon shell and the electrolyte, thereby accelerating the diffusion kinetics of lithium ions; ⑥ Amorphous SiO x Compared to crystalline pure silicon, the lower volume expansion rate and better isotropic expansion properties, combined with the confinement buffering effect of the external dual carbon structure, further ensure the stability of the electrode. Attached Figure Description
[0013] Figure 1 The SiO obtained in Example 1 of this invention x Scanning electron microscope image of the / NCNF@NC composite anode material.
[0014] Figure 2 The SiO obtained in Example 1 of this invention x / Transmission electron microscope image of the NCNF@NC composite anode material coating layer.
[0015] Figure 3 The SiO obtained in Example 1 of this invention x / NCNF@NC composite anode material SiO x High-resolution transmission electron microscope image of the particle edge.
[0016] Figure 4 The SiO obtained in Comparative Example 1 of this invention x Scanning electron microscope image of the / NCNF composite anode material.
[0017] Figure 5 Comparative Example 2 of this invention is pure SiO x Scanning electron microscope image of particles.
[0018] Figure 6 The SiO obtained in Example 1 of this invention x Cyclic stability test curves of / NCNF@NC and Comparative Example 2 at a current density of 0.2 A / g. Detailed Implementation
[0019] The principles and features of the present invention are described below with reference to embodiments. The examples listed are only for explaining the present invention and are not intended to limit the scope of the present invention.
[0020] Example 1 1) SiO x Preparation of PAN composite fibers: 0.2 g of amorphous silica particles were weighed and placed in 5 mL of DMF, and ultrasonically dispersed for 1 h. 0.6 g of PAN was added and dissolved in the dispersion. The dispersion was ultrasonically dispersed and magnetically stirred for 12 h at room temperature to obtain a uniformly mixed spinning solution. The spinning solution was transferred to a syringe, and electrospinning was performed under a high voltage of 12 kV, a feed rate of 0.5 mL / h, and a receiving distance of 15 cm. After drying, SiO₂ was obtained. x / PAN composite fiber; 2) SiO x Preparation of PAN@PANI composite fibers: 5 mL of aniline monomer and 1 mL of concentrated hydrochloric acid were added to 150 mL of deionized water and magnetically stirred to form a homogeneous monomer solution. The SiO2 prepared and cut in step 1) was then added to the solution. x The PAN fiber membrane was completely immersed in the monomer solution and allowed to stand at room temperature for 3 hours to achieve adsorption stability. Then, an oxidant solution was slowly added dropwise to the reaction system. This oxidant solution was prepared by dissolving 5 g of ferric chloride in 50 mL of deionized water containing 1.5 mL of concentrated hydrochloric acid. The polymerization reaction was carried out at room temperature for 8 hours. After the reaction, the product was washed and dried to obtain SiO₂. x / PAN@PANI composite fiber; 3) Multi-stage pre-oxidation stabilization treatment: The dried SiO2 from step 2) is then subjected to a multi-stage pre-oxidation stabilization treatment. x The PAN@PANI composite fiber membrane was placed in a muffle furnace and subjected to multi-stage pre-oxidation treatment in an air atmosphere. It was heated to 90 °C at a heating rate of 3 °C / min and held for 0.5 h. Then, it was heated to 180 °C at a heating rate of 3 °C / min and held for 0.5 h. Finally, it was heated to 270 °C at a heating rate of 3 °C / min and held for 2 h. After the treatment, it was cooled with the furnace to obtain the stabilized pre-oxidized product. 4) SiO x Preparation of / NCNF@NC composite anode material: The SiO2 prepared in step 3) was heated at a rate of 5 ℃ / min. x The PAN@PANI composite fiber is heated to 800 ℃ under an inert gas protective atmosphere and held for 2 h. After cooling in the furnace, a nitrogen-doped carbon-coated amorphous silicon suboxide / carbon nanofiber composite anode material can be obtained.
[0021] Example 2 1) SiO x Preparation of PAN composite fibers: carried out according to Example 1; 2) SiO x Preparation of PAN@PANI composite fibers: 5 mL of aniline monomer and 1 mL of concentrated hydrochloric acid were added to 150 mL of deionized water and magnetically stirred to form a homogeneous monomer solution. The SiO2 prepared and cut in step 1) was then added to the solution. x The PAN fiber membrane was completely immersed in the monomer solution and allowed to stand at room temperature for 3 hours to achieve adsorption stability. Then, an oxidant solution was slowly added dropwise to the reaction system. This oxidant solution was prepared by dissolving 5 g of ferric chloride in 50 mL of deionized water containing 1.5 mL of concentrated hydrochloric acid. The polymerization reaction was carried out at room temperature for 4 hours. After the reaction, the product was washed and dried to obtain SiO₂. x / PAN@PANI composite fiber; 3) Multi-stage pre-oxidation stabilization treatment: carried out according to Example 1; 4) SiO x Preparation of / NCNF@NC composite anode material: carried out according to Example 1.
[0022] Example 3 1) SiO x Preparation of PAN composite fibers: carried out according to Example 1; 2) SiO x Preparation of PAN@PANI composite fibers: 5 mL of aniline monomer and 1 mL of concentrated hydrochloric acid were added to 150 mL of deionized water and magnetically stirred to form a homogeneous monomer solution. The SiO2 prepared and cut in step 1) was then added to the solution. x The PAN fiber membrane was completely immersed in the monomer solution and allowed to stand at room temperature for 3 hours to achieve adsorption stability. Then, an oxidant solution was slowly added dropwise to the reaction system. This oxidant solution was prepared by dissolving 5 g of ferric chloride in 50 mL of deionized water containing 1.5 mL of concentrated hydrochloric acid. The polymerization reaction was carried out at room temperature for 12 hours. After the reaction, the product was washed and dried to obtain SiO₂. x / PAN@PANI composite fiber; 3) Multi-stage pre-oxidation stabilization treatment: carried out according to Example 1; 4) SiO x Preparation of / NCNF@NC composite anode material: carried out according to Example 1.
[0023] Comparative Example 1: 1) SiO x Preparation of PAN composite fibers: carried out according to Example 1; 2) Pre-oxidation stabilization treatment: The dried SiO2 from step 1)x / PAN composite fibers are placed in a muffle furnace and pre-oxidized in an air atmosphere. Specifically, the process includes heating to 280 ℃ at a heating rate of 2 ℃ / min and holding at that temperature for 2 h. After the process is completed, the fibers are cooled in the furnace to obtain a stabilized pre-oxidized product. 3) SiO x Preparation of / NCNF composite anode material: The SiO2 prepared in step 2) was heated at a rate of 5 °C / min. x The PAN composite fiber membrane is heated to 800 °C under an inert gas protective atmosphere and held for 2 h for heat treatment. After cooling in the furnace, the amorphous silicon suboxide / nitrogen-doped carbon nanofiber composite anode material can be obtained.
[0024] Comparative Example 2: Silica (2000 mesh, 99.99%) from Shanghai McLean Company.
[0025] Performance testing and results analysis: (1) Preparation of button cells: The samples of the examples and comparative examples to be tested were first dried in a vacuum oven at 60°C for 12 hours. Then, the samples were cut into 14 mm diameter silicon-carbon composite fiber electrode sheets as working electrodes using an MSK-T10 manual slicer. A 18 mm diameter polypropylene (Celgard PP 2500) membrane and a 16 mm diameter lithium sheet were used as the counter electrode. The electrolyte was KLD-LP46 lithium-ion electrolyte purchased from KLD, with a main component of 1 mol / L. -1 LiPF6 was dissolved in ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) (volume ratio 1:1:1), with 10 wt% fluoroethylene carbonate (FEC) added. One side of the battery was assembled in the order of negative electrode shell, spring sheet, gasket, and lithium sheet. The other side was assembled in the order of positive electrode shell, working electrode, and PP2500 separator. During assembly, 15 μL of electrolyte was dropped onto the surface of the lithium sheet and the working electrode. The positive electrode shell was then flipped over onto the negative electrode shell to complete the assembly. The batteries were then sealed using a small hydraulic button cell sealing machine (MSK-110). Finally, the sealed button cells were placed in a Blue Battery Testing System (CT2001A) in static mode for 24 hours to allow the electrolyte to fully wet the positive and negative electrodes before relevant electrochemical tests were performed.
[0026] To compare electrochemical performance, a pure micron-sized silicon suboxide electrode (Comparative Example 2) was prepared as a control group. The active material of Comparative Example 2 was micron-sized SiO₂. xThe binder sodium alginate (ALG) and conductive carbon black were mixed and ground in a mass ratio of 6:2:2. Then, distilled water was added as a solvent (solid-liquid mass ratio controlled at 1:9), and the mixture was thoroughly mixed and dispersed using a magnetic stirrer / ball mill to obtain a uniform electrode slurry. The slurry was then uniformly coated onto a smooth and clean copper foil current collector surface using a heated wire rod coating tester (ZY-TB-A2). After coating, the slurry was first pre-dried in a forced-air oven for 2 hours to remove most of the solvent, and then transferred to a 60°C vacuum oven for continuous drying for 24 hours to completely remove residual moisture. The stamping and battery assembly process was completely consistent with that of the composite electrode described above.
[0027] (2) Electrochemical performance test: In an environment of 25-28℃, a constant current charge-discharge test was performed using the Blue Electric test system (CT2001A), with the voltage window set to 0.005-2 V (vs. Li / Li). + The nominal specific capacity was set to 1000 mAh / g, and the charge / discharge current density was 0.2C. Rate performance was tested by performing 10 charge / discharge cycles at 0.1C, 0.2C, 0.5C, 1C, and 2C, followed by 10 charge / discharge cycles at 0.1C to verify the reversible capacity recovery capability. Table 1 shows the initial capacity measured at 0.2C, the capacity retention after 200 cycles, the capacity measured at 2C, and the capacity retention at 2C relative to 0.2C for each embodiment and comparative example.
[0028]
[0029] (3) Results Analysis The results in Table 1 show that the nitrogen-doped carbon-coated amorphous silicon suboxide / nitrogen-doped carbon nanofiber composite anode material prepared in Example 1 has a higher initial specific capacity and the best cycle stability. Compared with Comparative Example 2, the capacity decay during cycling and under high current charge-discharge conditions are significantly reduced in all examples and Comparative Example 1, indicating that confining micron-sized amorphous silicon suboxide particles in a bilayer carbon network can greatly improve the cycle stability of the material. All examples show higher capacity retention after 200 cycles and under 2C high-current charge-discharge conditions than Comparative Example 1 without a nitrogen-doped carbon shell, which fully demonstrates that the external coating layer can further resist SiO2 degradation during charge-discharge processes. x The volume expansion improves the stability of the electrode material, and also indicates that the coating layer can further improve the wettability of the material and electrolyte through the nitrogen atom doping effect, as well as through the SiO2 doping effect. xComplete coverage of the original fiber network effectively reduces contact resistance. Compared with Comparative Example 1, Example 1 shows a significant improvement in initial capacity, cycle capacity retention, and charge-discharge capacity retention under high current, indicating that the nitrogen-doped carbon shell double-shell conductive network has higher lithium storage efficiency than the uncoated single carbon fiber network. Example 1 exhibits the best performance compared to Examples 2 and 3, demonstrating that precise control of the appropriate polyaniline coating thickness is crucial for forming a high-quality graphitized carbon skeleton and thus improving the electrochemical performance of the material. The above examples are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made according to the spirit and essence of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A nitrogen-doped carbon-coated amorphous silicon suboxide / carbon nanofiber composite anode material, characterized in that, The composite anode material exhibits a three-dimensional network fiber structure, with nitrogen-doped carbon nanofibers (NCNF) formed by carbonizing polyacrylonitrile (PAN) fibers serving as the internal conductive framework, and amorphous silicon suboxide (SiO2) as the substrate. x The particles are uniformly dispersed within the fiber network structure, including NCNF and SiO. x The outer surface of the particles is coated with a nitrogen-doped carbon layer (NC) derived from the in-situ polymerization of polyaniline (PANI) followed by high-temperature carbonization and decomposition. The particle size of the amorphous silicon suboxide particles is 0.05-10 μm, the diameter of the fibers is 100-600 nm, and the thickness of the nitrogen-doped carbon layer is 5-50 nm. Based on the total mass of the composite negative electrode material as 100%, the mass percentage of amorphous silicon suboxide particles is 50-70 wt%, and the mass percentage of carbon is 30-50 wt%.
2. A method for preparing nitrogen-doped carbon-coated amorphous silicon suboxide / carbon nanofiber composite anode material according to claim 1, characterized in that, The preparation process includes the following steps: ①SiO x Preparation of PAN composite fibers: Weigh 0.2-1 g of amorphous silica particles and place them in 5-10 mL of DMF. Disperse ultrasonically for 1-2 h. Add 0.5-2.0 g of PAN and dissolve it in the dispersion. Disperse ultrasonically at room temperature and stir magnetically for 10-20 h to obtain a uniformly mixed spinning solution. Transfer the spinning solution to a syringe and perform electrospinning at a high voltage of 10-25 kV, a feed rate of 0.5-2.0 mL / h, and a receiving distance of 10-25 cm. After drying, obtain SiO₂. x / PAN composite fiber; ②SiO x Preparation of PAN@PANI composite fibers: Measure 3-8 mL of aniline monomer and 0.5-2 mL of concentrated hydrochloric acid and add them to 100-200 mL of deionized water. Stir magnetically to mix evenly and form a monomer solution. Add the SiO2 prepared and cut in step ①... x The PAN fiber membrane was completely immersed in the monomer solution and allowed to stand at room temperature for 1-5 hours to achieve adsorption stability. Then, an oxidant solution was slowly added dropwise to the reaction system. This oxidant solution was prepared by dissolving 3-8 g of ferric chloride in 30-80 mL of deionized water containing 1-3 mL of concentrated hydrochloric acid. The polymerization reaction was carried out at room temperature for 6-12 hours. After the reaction, the product was washed and dried to obtain SiO₂. x / PAN@PANI composite fiber; ③ Multi-stage pre-oxidation stabilization treatment: The SiO2 dried in step ② x The PAN@PANI composite fiber membrane was placed in a muffle furnace and subjected to multi-stage pre-oxidation treatment in an air atmosphere. The temperature was increased to 80-110 ℃ at a heating rate of 1-5 ℃ / min and held for 0.5-2 h. Then, the temperature was increased to 150-200 ℃ at a heating rate of 1-5 ℃ / min and held for 0.5-2 h. Finally, the temperature was increased to 250-300 ℃ at a heating rate of 1-5 ℃ / min and held for 1-4 h. After the treatment, the membrane was cooled with the furnace to obtain the stabilized pre-oxidized product. ④SiO x Preparation of / NCNF@NC composite anode material: The pre-oxidized product prepared in step ③ is heated to 700-1000 ℃ under an inert gas protective atmosphere at a heating rate of 1-5 ℃ / min and heat-treated for 2-6 h. After cooling with the furnace, nitrogen-doped carbon-coated amorphous silicon suboxide / carbon nanofiber composite anode material can be obtained.